179 WHAT MATTERS TO THE FRAIL OLDER PERSON CHANGES DURING COVID-19 AND SHOULD INFORM PATIENT CENTRED CHANGE. (18th November 2021) - Murphy, R; Sayers, K; Ryan, S; Maher, J; Pillay, I
Abstract: Background: 'What Matters to You'(WMTY) is a routine question in the comprehensive geriatric assessment (CGA) of the frail older person. The aim was to categorise WMTY and investigate changes during COVID-19. Methods: WMTY, clinical frailty score (CFS), age, gender, vision and hearing impairment, malnutrition risk, modified Barthel Index (mBI), living alone status, 4AT and dementia screening results were prospectively entered onto MS Excel. Answers were retrospectively categorised and compared, pre-COVID-19 (April to June 2019) and during COVID-19 (April to June 2020). Descriptive statistics and MS Excel T-test were used for data analysis. Results: The mean CFS (5), age (82 years), male: female ratio (1:1.3), prevalence of visual and hearing impairment (20–30%) and malnutrition risk were similar (23%) in both groups mBI was non-significantly reduced by a 1 point average during COVID-19. Less patients lived alone during COVID-19 (p = 0.05). Positive delirium screen doubled (12% vs 26%) during COVID-19. Positive dementia screen doubled (10% vs 20%) during COVID-19. Themes in decreasing order were family, health, home, functional independence, pets, discharge plan, religion, work, social activities and other pre-COVID-19. Family and health accounted for 49% of responses. During COVID-19, the order changed to health, family and home, functional independence, work and discharge planning, pets, religion and social activities. There was a 50% increase in functional independence as a response, a 40% increase in home and a 58% decrease in family as a response. Conclusion: Cognitive vulnerability doubled during COVID-19. Nine themes were identified. WMTY themes shifted during COVID-19. Health become the most frequent response. Family became a less frequent response with less people living alone. Functional independence was more frequent reflecting the need for self-reliance during COVID-19. Home, where all COVID-19 life was lived, was expressed as WMTY by a greater number of respondents. Promotion of functional independence has been identified as a key driver for practice change.